Luteal function in cyclic goats treated with human chorionic gonadotropin administered by intramuscular or intravaginal routes at the time of artificial insemination - Rodrigues, Juliana Nascimento Duarte; Guimarães, José Domingos; Rangel, Paulo Sérgio Cerqueira; Oliveira, Maria Emilia Franco [UNESP]; Brandão, Felipe Zandonadi; Bartlewski, Pawel Mieczyslaw; Fonseca, Jeferson Ferreira (Wiley, 2023)
Human chorionic gonadotropin (hCG) has been used to improve goats reproductive efficiency. This study aimed to (i) evaluate if hCG administered by the intramuscular (i.m.) or intravaginal (i.vag.) route can be detected by a rapid β-hCG test in blood plasma samples and (ii) document ovarian effects of hCG administered by both routes at the time of artificial insemination (AI) performed 60 h after oestrus synchronization in goats. Twenty-two Alpine goats received two i.m. injections of 30 μg of d-cloprostenol (Prolise®, Tecnopec, São Paulo, Brazil) 7.5 days apart. One day after the onset of oestrus (at the time of AI), the goats were randomly allocated to one of the three groups that received: control (n = 7): 0.3 ml of saline solution intravaginally; hCGi.m. (n = 7): 300 IU of hCG (Vetecor®; Hertape-Calier, São Paulo, Brazil) i.m. and hCGi.vag. (n = 8): 300 IU of hCG deposited intravaginally. Blood samples were drawn at −1, 3, 6, 9 and 24 h after as well as on days 3, 7, 10, 13, 17 and 21 after hCG treatment/AI. All animals tested negative for hCG (ECO Diagnóstica, Corinto, Brazil) at −1 h, and all control animals tested negative throughout the entire blood collection period. All hCGi.m. animals tested positive from 3 h until D3 post-AI but only 50% of hCGi.vag. goats tested positive during the present study. In all animals studied, mean circulating P4 concentrations increased (p <.05) from D3 to D7 after AI and then declined (p <.05) from D10 to D17 in control and hCGi.m. groups and from D17 to D21 in the hCGi.vag. group. Total cross-sectional luteal area (CLA), mean colour Doppler area (DA), DA/CLA, mean high-velocity Doppler area and HVDA/CLA all declined (p <.05) by D17–D21 in all animals studied. In summary: (i) human chorionic gonadotropin could consistently be detected in blood samples using the rapid β-hCG test only in the hCGi.m. group; and (ii) there were no significant differences in the mean pregnancy rate, circulating P4 concentrations and various luteal parameters studied among Control, hCGi.m. and hCGi.vag. dose.
Keywords: corpus luteum; goat; hCG; luteal function; pregnancy rates; ultrasonography